Exploring Relationship between Saudi EFL Learners’ Attitude to CALL in Listening and Their Prior Experience with CALL Integrated EFL Courses - Shahid, Shahid Hussain; Zuraina, Ali; Mahmoud, Masoud Omar (IOSR Journals, 2017)
As an integral part of communication, listening holds a key place in a language and it plays a vital role in the language acquisition process. However, its development has been a big challenge for language teachers. CALL seems to have solved this problem but its successful integration largely depends on students‘ positive attitude towards it. The present study aimed to investigate Saudi EFL learners attitude toward use of CALL in listening comprehension from the perspective of their prior experience with CALL integrated EFL courses. A two-part questionnaire was administered amongst 30 participants at Majmaah University, Saudi Arabia. The first 10 items part to collect demographic information and the last 30 items aimed to investigate their attitude to CALL in listening comprehension. Data were analyzed employing descriptives, one-way ANNOVA, and Pearson‘s r correlation techniques. The findings revealed students had positive attitude toward use of CALL in listening comprehension. Furthermore, significant difference in attitudes was also noted based on their prior experience with CALL. In addition, there was a significant correlation between students‘ attitude toward using CALL in listening and their prior experience with CALL integrated EFL courses.